Trends and Patterns in Passenger Traffic in Aviation Sector: A Comparative Study of BRICS Countries - et al., Ankita Pareek (International Journal of Advanced Science and Technology, 2019)
The study examines the trends and patterns in passenger traffic in five emerging economies i.e. Brazil, Russia, India, China and South Africa. It studies monthly and yearly data for the past 24 years and tries to examine the patterns of growth in the selected countries. The Compound annual growth rate (CAGR) was calculated to see the differences in passenger growth followed by paired student-t test to see if significant differences exist between the mean values. The results revealed interesting trends for Airline Industry in general and more specifically for Indian Aviation sector. The results reveal significant scope of growth in Indian aviation sector in future especially due to low current level of penetration. Further, the low fuel price and favorable government policy, exchange rate and improved liquidity provide indications of brighter prospects for Aviation sector in the near future.